Progress in Diagnosing Mitochondrial Myopathy, Encephalopathy, Lactic Acidosis, and Stroke-like Episodes - Wang, Ying-Xin (Chin Med J (Engl), 2015)
OBJECTIVE: Mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) is a progressive, multisystem affected mitochondrial disease associated with a number of disease-related defective genes. MELAS has unpredictable presentations and clinical course, and it can be commonly misdiagnosed as encephalitis, cerebral infarction, or brain neoplasms. This review aimed to update the diagnosis progress in MELAS, which may provide better understanding of the disease nature and help make the right diagnosis as well. DATA SOURCES: The data used in this review came from published peer review articles from October 1984 to October 2014, which were obtained from PubMed. The search term is “MELAS”. STUDY SELECTION: Information selected from those reported studies is mainly based on the progress on clinical features, blood biochemistry, neuroimaging, muscle biopsy, and genetics in diagnosing MELAS. RESULTS: MELAS has a wide heterogeneity in genetics and clinical manifestations. The relationship between mutations and phenotypes remains unclear. Advanced serial functional magnetic resonance imaging (MRI) can provide directional information on this disease. Muscle biopsy has meaningful value in diagnosing MELAS, which shows the presence of ragged red fibers and mosaic appearance of cytochrome oxidase negative fibers. Genetic studies have reported that approximately 80% of MELAS cases are caused by the mutation m.3243A>G of the mitochondrial transfer RNA (Leu (UUR)) gene (MT-TL1). CONCLUSIONS: MELAS involves multiple systems with variable clinical symptoms and recurrent episodes. The prognosis of MELAS patients depends on timely diagnosis. Therefore, overall diagnosis of MELAS should be based on the maternal inheritance family history, clinical manifestation, and findings from serial MRI, muscle biopsy, and genetics.